The Training Development Curriculum Cognitive Skills for The Elderly - สว่างวรนาถ, กิตติ์ธเนศ; ครุฑกะ, ชมสุภัค (Journal of The Royal Thai Army Nurses, 2019)
In this dissertation, the researcher studies (1) how the elderly use necessary cognitive skills in addition to developing (2) a cognitive skills training curriculum for the elderly. Finally, furthermore (3) the curriculum developed by the researcher is evaluated. The sample population consisted of 420 elderly persons who were participants in Elderly Clubs at Public Health Centers in Bangkok Metropolis. The research instrument was a questionnaire eliciting data appertaining to the necessary cognitive skills of the elderly, The curriculum developed and constructed, and a self-evaluation questionnaire concerning cognitive skills. The researcher analyzed in terms of mean (M), standard deviation (SD) and t test dependent. The research finding: (1) The elderly exhibited levels of opinions regarding international competencies in an overall picture and in all aspects at a high level. (2) The development of training curriculum cognitive skills of seniors that includes course outlines the problems and needs. The goal-oriented behavior this sort of content learning activities how to measure and evaluate curriculum consists of learning units 4 units, each unit consisting of (1) the elderly with changing health status, (2) the health of the elderly (3) solving the problem of the elderly (4). adaptation of the elderly the checks are appropriate to the level and the most consistent of all the elements. (3) Seniors are cognitive skills, overall and after using the formula training than before training curriculum at a statistically significant level. 05. The elderly participants were satisfied to take a training course to improve their overall cognitive at a high level.